PENGEMBANGAN DESAIN PEMBELAJARAN SPLDV BERBASIS PBL UNTUK MENINGKATKAN KEMAMPUAN KOMUNIKASI MATEMATIS PESERTA DIDIK KELAS VIII SMP - muyassar a'la; I Made Arnawa (UNIVERSITAS MUHAMMADIYAH METRO, 2023)
The difficulty of educators in designing interesting learning paths for students makes students tend to lack understanding of mathematics. The learning flow used tends to ask students to remember the